The Internet of Toys Practices, Affordances and the Political Economy of Children's Smart Play - Mascheroni, Giovanna; Holloway, Donell (Studies in Childhood and Youth,, 2019)
The Internet of Toys (IoToys) is a developing market within our Internet of Things (IoT) ecosystem. This book examines the rise of internet-connected toys and aims to anticipate the opportunities and risks of IoToys before their widespread diffusion. Contributors to this volume each provide a critical analysis of the design, production, regulation, representation and consumption of internet-connected toys. In order to address the theoretical, methodological and policy questions that arise from the study of these new playthings, and contextualise the diverse opportunities and challenges that IoToys pose to educators, families and children themselves, the chapters engage with notions of mediatization, datafication, robotification, connected and post-digital play. This timely engagement with a key transformation in children's play will appeal to all readers interested in understanding the social uses and consequences of IoToys, and primarily to researchers and students in children and media, early childhood studies, media and communications, sociology, education, social psychology, law and design. .